Breasts and Lymphatic Tissue ; A Literature Review - Muhammad Iqbal; Wirsma Arif Harahap (Journal of Midwifery, 2020)
The breasts begin to grow from the sixth week of the embryo in the form of ectodermal thickening along the milk line that lies from the axilla to the middle of the groin (inguinal). The blood supply comes from the internal mammary artery, which is a branch of A. subclavian. Additional bleeding originated from A. axillary through the branches of A. thoracic lateral, A. thoraco dorsalis, and A. thoraco acromialis. The return of blood through the veins follows the passage of the artery to the internal mammary V. and the axillary vein branches to the superior V. kava. Lymph capillaries are located under the epidermis with a diameter between 20 and 70 mm. Lymphangion, as a pacemaker is limited by valves and lymphatic endothelial cells, will initiate an intrinsic pulsation of lymph fluid flow. Extrinsic factors such as contraction of the skeletal muscles, massage, increased hydrostatic pressure by postural gravity can also affect the lymphatic flow rate.5,6 These lymphatic vessels run on the lateral side of the upper arm, parallel to the cephalic vein and drain into the supraclavicular nodes. 4 The LVC is an important anatomical structure for the physiology of vascular lymph node transplantation (VLNT) .8 Lymph vessels in the upper limb travel axially from the fingers to the back of the hand and make direction to the elbow, travel to the anteromedial area at the top of the arm and connect to the axillary lymph nodes in the lateral area. An alternative route directly to the supraclavicular node can be identified. These lymphatic vessels run on the lateral side of the upper arm, parallel to the cephalic veins and drain into the supraclavicular nodes. 4 The LVC is an important anatomical structure for the physiology of vascular lymph node transplantation (VLNT) .8An alternative route directly to the supraclavicular node can be identified. These lymphatic vessels run on the lateral side of the upper arm, parallel to the cephalic veins and drain into the supraclavicular nodes. 4 An alternative route directly to the supraclavicular node can be identified. These lymphatic vessels run on the lateral side of the upper arm, parallel to the cephalic veins and drain into the supraclavicular nodes.